2019
DOI: 10.1523/eneuro.0189-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Dynamics of Inhalation-Linked Activity across Defined Subpopulations of Mouse Olfactory Bulb Neurons ImagedIn Vivo

Abstract: In mammalian olfaction, inhalation drives the temporal patterning of neural activity that underlies early olfactory processing. It remains poorly understood how the neural circuits that process incoming olfactory information are engaged in the context of inhalation-linked dynamics. Here, we used artificial inhalation and two-photon calcium imaging to compare the dynamics of activity evoked by odorant inhalation across major cell types of the mouse olfactory bulb (OB). We expressed GCaMP6f or jRGECO1a in mitral… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 61 publications
1
34
0
Order By: Relevance
“…To date, sniff-coupled activity in MCs and TCs has been described using both electrophysiological (Adrian, 1950 ; Cang and Isaacson, 2003 ; Margrie and Schaefer, 2003 ; Carey and Wachowiak, 2011 ; Shusterman et al, 2011 ; Smear et al, 2011 ; Fukunaga et al, 2012 , 2014 ; Igarashi et al, 2012 ; Díaz-quesada et al, 2018 ; Jordan et al, 2018a , b ) and imaging techniques (Iwata et al, 2017 ; Short and Wachowiak, 2019 ; Eiting and Wachowiak, 2020 ) in a variety of brain states. However, it is unclear how sniff-locking under wide-ranging protocols relates to each other, especially given that parameters of sniff patterns, or inputs to the olfactory system, can change drastically between anesthetized and awake states (Welker, 1964 ; Jessberger et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, sniff-coupled activity in MCs and TCs has been described using both electrophysiological (Adrian, 1950 ; Cang and Isaacson, 2003 ; Margrie and Schaefer, 2003 ; Carey and Wachowiak, 2011 ; Shusterman et al, 2011 ; Smear et al, 2011 ; Fukunaga et al, 2012 , 2014 ; Igarashi et al, 2012 ; Díaz-quesada et al, 2018 ; Jordan et al, 2018a , b ) and imaging techniques (Iwata et al, 2017 ; Short and Wachowiak, 2019 ; Eiting and Wachowiak, 2020 ) in a variety of brain states. However, it is unclear how sniff-locking under wide-ranging protocols relates to each other, especially given that parameters of sniff patterns, or inputs to the olfactory system, can change drastically between anesthetized and awake states (Welker, 1964 ; Jessberger et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…This renewed interest in the coordination of rodent orofacial motor behaviors has led to the development of novel technologies for measuring rodent breathing and sniffing [19,20], which are complementary to the method described here. Recent work has further emphasized the importance of sniff dynamics for odor identity coding and discrimination [1,[21][22][23], augmented by new analytical approaches to analyzing olfactory network dynamics, particularly the use of time warping [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…For OB projection neurons, however, only little information about chemotypes is available at this point: Pcdh1 and Tbx21 (Haddad et al, 2013;Nagai et al, 2005) have been shown to be selectively expressed in a subset of OB projection neurons. CCK distinguishes a subset of TCs (superficial TCs, (Liu and Shipley, 1994;Seroogy et al, 1985;Short and Wachowiak, 2019;Sun et al, 2020); vasopressin expressing cells might constitute a further subset of superficial TCs (Lukas et al, 2019). Heterogeneous expression of both the GABAa receptor as well as voltage-gated potassium channel subunits have been observed (Padmanabhan and Urban, 2010;Panzanelli et al, 2005), albeit not linked to specific cell types.…”
Section: Introductionmentioning
confidence: 99%